Physiotherapy Treatment for Gangrene Wound Patients Using Transcutaneous Electrical Nerve Stimulation (Tens) and Interferential Current (IFC) at the Miftachul Munir Medika Clinic Surabaya - Efi Kurniawati, Efi Kurniawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
Diabetes mellitus is included in the disease of the silent killer where most sufferers realize when the disease starts to get worse, when the disease starts to worsen, there will be some complications between the complications is diabetic retinopathy, diabetic nephropathy, neuropathy. The problem that often arises in people with diabetes mellitus is the wound of diabetes mellitus which can be caused due to vascular disorders, nerve disorders and the presence of infection, if the wound is not taken seriously, it will be a source of amputation. Electrical stimulation has been used to improve chronic wound healing in the United States for almost four decades, Transcutaneous Electrical Nerve Stimulation (TENS) and Interferential Current (IFC) including electrical stimulation that can help in healing wounds including diabetic wounds. The purpose of this study was to determine the differences in the effect of wound healing due to diabetes mellitus by the intervention of Transcutaneous Electrical Nerve Stimulation (TENS) and Interferential Current (IFC). The research method used in this study was quasi experimental with research design pretest and posttest without control. The population of this study were all 4 patients who arrived at di klinik miftachul munir medika surabaya during November 2021-desember 2021 as many as 4 people according to the criteria of inclusion and exclusion where 2 people were given TENS and 2 people were given IFC intervention. This research was conducted twice a week for 4 weeks and measured using the Bates-Jansen Wound Assessment Tools scale. The results of this study were 2 people who were given TENS experienced wound healing of 13.5% while 2 people given IFC experienced wound healing of 34%. The difference in wound healing in this study was 20.5%. It can be concluded that IFC is good in the process of wounds healing due to diabetes Miletus.